DEVICE FOR SIMULATING OF ELECTROSTATIC DISCHARGE BY THE EXPLORATION OF NOISE STABILITY OF RADIOELECTRONIC TECHNICS - V. V. Dybrovskij; O. U. Gapanovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the original development and analysis of the functioning of the device for simulation of electrostatic discharges, which can be used in a wide range of test systems is presented.